Review of Leda Papastefanaki and M. Erdem Kabadayı, eds., Working in Greece and Turkey: A Comparative Labour History from Empires to Nation-States, 1840–1940 - Ginio, Eyal (Historein, 2023)
Review of Leda Papastefanaki and M. Erdem Kabadayı, eds., Working in Greece and Turkey: A Comparative Labour History from Empires to Nation-States, 1840–1940. New York and Oxford: Berghahn, 2020. xviii + 468 pp.